The examination of the psychometric properties of the Turkish Collective Efficacy Questionnaire for Sports - Erman Öncü; Deborah L. Feltz; Cathy D. Lirgg; Bülent Gürbüz (Palacký University Olomouc, 2018)
Background: Current research has demonstrated a consistent and positive relationship between collective efficacy and group performance in organizational settings, including sports. However, there is still a need for the development of scales measuring this relationship in order to clarify the scientific shortcomings. Objective: The current study analyzed the psychometric properties of the Turkish version of the Collective Efficacy Questionnaire for Sports (T-CEQS). Methods: The sample consisted of 522 college-age student-athletes (176 women, 346 men) from different universities in Turkey with a mean age of 21.40 years (SD = 2.11). The CEQS consists of 20 items, with five subscales. A confirmatory factor analysis was used to test the factor structure. Pearson's product-moment coefficients were used to assess the correlations between the CEQS factors and the Collective Self-Efficacy Scale (CES). Cronbach's alphas were calculated for the subscales in order to evaluate their internal consistency. Results: The results confirm the 5-factor internal structure of the T-CEQS. The results of the correlation analysis between the T-CEQS subscales and the CES indicated significant and positive relationships. We also found acceptable values of the alpha coefficient (between .70 and .85), which confirms the T-CEQS as a reliable instrument. Conclusions: The T-CEQS is a relatively short questionnaire that allows researchers to measure team efficacy beliefs across sports. It also is a multidimensional state measure, based on current capabilities, not potential capabilities or expected future capabilities. The present findings provide preliminary support for the utility of the T-CEQS as a measure for assessing collective efficacy in Turkish sport teams prior to competitions.